Analyse des formes et des fonctions d’acte de langage assertif sur les articles d’écologie dans le magazine Mademoiselle - Putri Adelia Rambe; Tengku Ratna Soraya (Didacticofrancia Journal Didactique du FLE, 2026)
This research analyzes assertive speech acts in three ecological articles from the magazine Mademoiselle (December 2023 - March 2024) using a descriptive qualitative method and a pragmatic approach. The study identifies five functions of assertive acts: declaring, suggesting, complaining, boasting, and demanding. Out of 45 acts identified, declaring dominates with 25 cases, followed by suggesting and complaining (6 cases each), then boasting and demanding (4 cases each). Eight predictive phrases are listed: three concerning climatic socio-economic risks for women (item 1), two on climate policies (item 2), and three scientific predictions about future extreme temperatures (item 3). The results reveal that predictive acts are used as communicative strategies to warn, raise awareness, and encourage climate action. This research demonstrates the strategic use of assertive speech acts in environmental discourse to influence readers’ perceptions and behaviors towards climate issues.